Analisis Tokoh Utama Pada Novel Si Anak Kuat Karya Tere Liye Dan Relevansinya Sebagai Pembelajaran Novel Di SMA (Psikologi Sastra) - Hidayati, Nurul Amalia; Mujtaba, Sahlan; Pratiwi, Wienike Dinar (Peneliti.net, 2024)
The aim of the research is to describe (1) The elements contained in the novel Si Anak Kuat by Tere Liye, (2) Study of literary psychology in the novel si Anak Kuat by Tere Liye. The method used is descriptive qualitative. The subject of the study is the novel Si Anak Kuat by Tere Liye which depicts the life struggles of a child in literary works. To make it more specific, there is a literary psychological theory explained, namely Sigmund Freud’s Theory (Id, Ego, Super ego). This novel story can be used as an alternative literature teaching material in high school because it suits students’ needs.